Schedule delay analysis of a UP construction project - Carreon, Kevin G.; Germar, Fernando J. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Inadequate or weak preparatory work before starting construction of any structure may cause serious problems during the construction period. For example, projects without sufficient detailed drawings or constmction schedules and a disorganized building site can create many problems in the management and completion of the construction works. Consequently, the cost of construction increases digressively, the construction duration of the project extends and the quality of construction is affected adversely. This study dwells on the importance of construction schedules in achieving the aim of producing good quality construction work within the specified duration. Monitoring continuously the interactive relation concerning delays in construction schedules and contractor demands is a complicated process. Here the simplest and basic approach is that, both for owner and contractor, time is money and for this reason construction schedule delays should be analyzed and corrective measures should be taken in a timely marmer. The main purpose of this study is to investigate the causes of construction schedule delays and the methods of schedule delay analyses. In this context, the first phase of construction works of a UP construction project was selected as a case study for analyzing project scheduling and the delays therein. The "Time Impact Analysis Method" (TIA) was applied to the case study project in order to determine the construction schedule delays and to measure the impacts of these delays on the project completion duration. After the application of the delay analysis and regeneration of the original schedule through MS Project 2013 , it was computed that the delays in the critical activities extended the project duration by 115 days in total i.e. by 95.83% of the estimated construction period. The delay was caused by unforeseeable weather conditions, delay in progress payment, and design changes by owner or his agent during construction.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Construction industry -- Management; Production scheduling